2016
DOI: 10.1590/0100-69912016006010
|View full text |Cite
|
Sign up to set email alerts
|

Emergency cricothyrotomy: temporary measure or definitive airway? A systematic review.

Abstract: Being a fast and safe method in the hands of well trained professionals in both prehospital and intrahospital care, Cricothyrotomy has been broadly recommended as the initial surgical airway in the scenario "can't intubate, can't ventilate", and is particularly useful when the obstruction level is above or at the glottis. Its prolonged permanence, however, is an endless source of controversy. In this review we evaluate the complications of cricothyrotomy and the need of its routine conversion to tracheotomy th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
(45 reference statements)
0
12
0
6
Order By: Relevance
“…Once stabilized, the airway will need conversion to tracheal tube or tracheostomy. 11,237 Pharyngeal or oesophageal injury may have occurred, with potential for mediastinal infection and may require further investigation. 223…”
Section: Management Following Fonamentioning
confidence: 99%
“…Once stabilized, the airway will need conversion to tracheal tube or tracheostomy. 11,237 Pharyngeal or oesophageal injury may have occurred, with potential for mediastinal infection and may require further investigation. 223…”
Section: Management Following Fonamentioning
confidence: 99%
“…In 1921 Jackson described that, in a series of 200 patients, nearly 80% of tracheal stenosis were secondary to the previous cricothyrotomy, warning against its use even in case of ESA necessity [34]. This is why conversion of emergency CT into a formal tracheostomy within 3 days has been suggested to avoid the establishment of pathologic mechanisms leading to the development of subglottic stenosis [35]. Since then, several studies later demonstrated a significant reduction in the risk of such postoperative complication [36,37], and current ATLS [24] and DAS guidelines [22] suggest surgical CT as a rescue procedure of choice for the establishment of an ESA in the CICO scenario.…”
Section: Esa: Should Emergency Tracheotomy Be Preferred Over Cricothymentioning
confidence: 99%
“…Traditionally, CTT was converted to formal TS within 72 h [33,38]. This statement was based upon the historical assumption that CTT is associated with an extremely high risk of subglottic stenosis [39].…”
Section: Conversion To Tracheostomymentioning
confidence: 99%
“…Moreover, there seems to be no significant difference in the complication rates of CTT and TS [ 41 ], while the incidence of late complications might be even higher with TS compared to CTT (25.1% vs. 13.6%) [ 33 ]. Various studies report the rate of conversion for CTT as ranging from 0–100% [ 38 ], without differences in terms of long-term benefits between the conversion and permanence of CTT [ 42 , 43 ]. However, considering the lack of experience of personnel in the postoperative care of CTT in comparison to TS in our wards as well as the higher risk of CTT cannula dislodgement and/or occlusion, in our opinion, conversion to a formal TS is strongly suggested.…”
Section: Commentsmentioning
confidence: 99%